Novel EDTA-ligands containing an integral perylene bisimide (PBI) core as an optical reporter unit - Marcia, Mario; Singh, Prabhpreet; Hauke, Frank; Maggini, Michele; Hirsch, Andreas (Organic & Biomolecular Chemistry, 2014)
The synthesis, characterization and metal complexation of a new class of perylene bisimides (PBIs) as an integral part of ethylenediaminetetraacetic acid (EDTA) are reported. The simplest representative, namely derivative 1a, was synthesized both by a convergent as well as a direct approach while the elongated derivatives, 1b and 1c, were obtained only via a convergent synthetic pathway. All these new prototypes of water-soluble perylenes are bolaamphiphiles and were fully characterized by H-1- and C-13-NMR spectroscopy, matrix assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry and IR spectroscopy. In order to acquaint ourselves with the behaviour in solution of our PBIs bearing dendritic wedges, the simplest derivative, 1a, was chosen and tested by means of UV/Vis and fluorescence spectroscopy as well as by zeta-potential measurements. A photoexcitation induced intramolecular photo-electron transfer (PET) can be observed in these molecules. Therefore their potential applications as sensors can be imagined. Model compound 1a efficiently coordinates trivalent metal cations both in water and dimethyl sulfoxide (DMSO). Significantly, the effects of the complexation strongly depend on the aggregation state of the PBI molecules in solution. As a matter of fact, in water, the presence of M3+ ions triggers the formation of light emitting supramolecular aggregates (excimers). On the other hand, in DMSO-rich solutions metal complexation leads to the suppression of the PET and leads to a strong fluorescence enhancement.